Features of forms of agro-industrial complex management in the sustainable development of agriculture - Kamenova, M.Zh.; Jazykbayeva, B.K.; Aymurzina, B.T. (BUKETOV BUSINESS REVIEW, 2019)
In the article it is noted that the choice of forms of management is an important problem of the existing economic relations in the agrarian sphere. The practice of reforms in the agro-industrial complex has shown that in Kazakhstan more than 80 % of gross output is currently produced by «households of the population» and peasant farms, ensuring a further increase in the volume of agricultural production, namely, plant growing and its economic efficiency. Currently in the agricultural sector, there is a tendency to small-scale production. As the situation showed, one of the main factors negatively affecting investment activity is the financial instability of most agricultural producers, the low level of its profitability and significant risks. The factors of low profit growth in the agricultural sector are related to the peculiarities of the demand for agricultural products and the seasonality of production in this industry. The analysis of the gross agricultural output of the Republic of Kazakhstan by the categories of farms, the profitability of agricultural production for 2012–2017 years was carried out, the influence of prices and grain yield on the level of farm income was shown. Suggestions for further improvement of grain pricing were given.